Combined light and electron microscope in routine histopathology. Issue 4 (April 1982) - Jones, S; Chapman, S K; Crocker, P R; Carson, G; Levison, D A
Abstract : We report our experience with a prototype combined light and electron microscope (the LEM 2000) with particular reference to its application to routine surgical histopathology. We found its major advantages over conventional transmission electron microscopies were due to the large grid size (7 mm diameter), low magnification capacity (x 250), and the built-in microprocessor for recording areas of interest. These features combine to reduce sampling errors and greatly facilitate orientation and relocation of fields of diagnostic importance.